Factors Influencing Students of Technology-Based Universities to Become Entrepreneurs - Badri-Harun, Azamudin; Mansor, Kamarul Ariffin; Hussain Shaari, Zullina; Zainol, Md Radzi; Amar, Amzairi (International Review of Management and Marketing, 2017)
Entrepreneurial activities, other than providing employment opportunity and help improved competitiveness, also becoming incubators of technological innovations. The investigation on factors influencing students of technology-based universities to become entrepreneurs is crucial as it enables the researcher to identify the contributing factors that might significantly influence these potential graduates to embark on entrepreneurial activities. In other words, the research could unravel the enabling factors of the undergraduate students to become entrepreneurs. The external elements being investigated were the role model and the role of the universities in promoting entrepreneurship. The study also focused on the internal elements which were views of achievement and views of personal control on the inclination to become entrepreneurs. The results of the analysis vary from one university to another. Nevertheless, the investigation reveals that for full data set, role model, views on achievement, and views on personal control have a positive significant relationship with an inclination of students to become entrepreneurs. Keywords: Entrepreneurship, Entrepreneurial Mindset, Entrepreneurship Education JEL Classifications: J23, L26, I23